The Political Economy of Cooperation in Renminbi (RMB) Internationalization Between China and the ASEAN States: Opportunity and Challenge. Issue 6 (1st November 2016) - Chao, Wen-Chih
Abstract : The main argument of this article is if the collaboration between China and ASEAN members on RMB internationalization can proceed smoothly? This study explored the opportunities and challenges of both parties in their cooperation on RMB internationalization. In the cooperating on internationalizing the RMB, China and ASEAN members have encountered opportunities that are both economic and political challenges. China's substantial economic growth and its stable currency are positive factors for China to cooperate with ASEAN. Nevertheless, several potential restraining factors remain that must be handled by both parties Economically, the uncertainties include whether China opens its capital account, how the Chinese financial market is developed, and how the economic hegemony of using the USD as a medium of exchange in bilateral transactions can be changed to using the RMB. Politically, territorial disputes, ideological differences, and the rapid growth of China's military power remain the potential obstacles to bilateral economic cooperation.